First radiation hardness results of the TeraPixel Active Calorimeter (TPAC) sensor - Price, T; Watson, N; Wilson, J; Rajovic, V; Cussans, D; Goldstein, J; Head, R; Nash, S; Page, R; Velthuis, J; Strube, J; Stanitzki, M; et al. (2013)
The TeraPixel Active Calorimeter (TPAC) sensor is a novel Monolithic Active Pixel Sensors (MAPS) device developed for use as the active layers of a large area, digital electromagnetic calorimeter (DECAL) at a future e +e- collider. Further applications, which include the tracking and vertex systems for future lepton colliders and LHC upgrades have been proposed and it is therefore essential to characterise the behaviour of the sensor for these applications. We present the first studies of radiation hardness testing of the TPAC sensor. The performance of the sensor has been evaluated after exposures up to 5 Mrad of 50 keV x-rays. Under realistic ILC operating conditions a maximum decrease in the signal to noise ratio of 8% (15%) was observed after 200 krad (5 Mrad) which is already sufficient for proposed applications in future e+e- colliders. © 2013 IOP Publishing Ltd.